Iban Language Education in the Digital Age: A Conceptual Review via MIDBI Model - Banseng, Saripah; Gerry, Doratya; Matt, Debbie Grace Frederick (Universitas Negeri Padang, 2025)
This article analyzes the development of Iban language education within the framework of the digital age, emphasizing the interaction among technology, pedagogy, and cultural factors. The Iban language faces challenges associated with modernization, digital readiness, and the preservation of cultural heritage in Malaysia. This study aims to conceptualize the improvement of Iban language instruction via digital innovation, while maintaining its cultural integrity. A qualitative conceptual literature review synthesized studies from 2010 to 2025, utilizing databases such as Scopus, ERIC, and MyJurnal. The text discusses Iban language education, indigenous pedagogy, digital transformation, and culturally sustaining teaching methodologies. The literature underwent thematic synthesis to identify recurring themes related to technological adaptation, pedagogical innovation, and cultural contextualization. The analysis employed established frameworks including Technological Pedagogical Content Knowledge (TPACK), Diffusion of Innovations Theory, and Culturally Sustaining Pedagogy. The findings indicate that effective Iban language education in the digital era requires a balanced integration of three dimensions, leading to the creation of the Model for Digital Integration of Iban Language (MIDBI). This study offers a conceptual framework for future empirical research and outlines implications for educators, policymakers, and curriculum developers focused on improving digital inclusion and cultural continuity in indigenous language education.